Control of Coexisting and Chaotic Attractors in Brushless Direct Current Motor - TSAFACK, ALEX STEPHANE KEMNANG; AINAMON, MARTIN PEPIN; CHEUKEM, ANDRE; PONE, JUSTIN ROGER MBOUPDA (My University, 2020)
Control of coexisting attractors and chaos in brushless direct current motor (BLDCM) is investigated in this paper. Using a weak harmonic modulation of a parameter of the BLDCM, the coexisting attractors between chaotic and period-1-oscillations are destroyed and transformed to period-1-oscillations. Moreover, two single controllers are designed to control the chaotic behavior found in BLDCM. Numerical simulations are used to evaluate the performance of the two developed controllers. Finally, the dynamical behaviors found in BLDCM and the physical feasibility of two proposed single controllers are validated through circuit implementations on OrCAD-PSpice software. The robustness of the three controllers is tested by a sensitivity analysis to parametric uncertainties.
Keywords: Brushless direct current motor · Chaotic attractor · Coexisting attractors · Weak harmonic modulation control; method · Chaos control · Circuit implementation